Purwarupa Cleaning Room Web Based ICU (Intensive Care Unit) - Predyus Fan Suhery; Ritzkal Ritzkal; Ade Hendrawan (Jurnal Mantik, 2020)
The Intensive Care Unit (ICU) is a part of an independent hospital (an agency under the director of service) a special room provided by the hospital, of course a very special room has special staff and special equipment with the aim of treating patients suffering from various diseases such as critical, injury or diseases that threaten life or potentially life threatening with the prognosis dubia. This room is very well maintained and maintained, for example, if someone wants to visit a patient who is sick who has been operated in the room (ICU), of course the conditions must be fulfilled by the visitor. For example the visitor must wash their hands and other provisions. In this study the authors designed and making a vacuum cleaner control prototype or commonly called a vacuum cleaner, to make it easier for hospital cleaning service workers, especially room cleaning services (ICU). The problem of this research is how to make a prototype tool that is controlled by Android and can send reports to the Web. This research includes several stages, the stages of analysis, the design stage, the implementation or implementation stage and the last stage is the testing stage. Current technological developments make it possible to automate the use of a vacuum cleaner which has been too troublesome in the manual way. Then an automatic vacuum cleaner was designed whose movement is directly controlled by the RC Control application, connected using Bluetooth and android we can control via Buton buttons which is already in the application, and in the application button there are several buttons that can be controlled such as the tool button moving back and forth, left and right and the vacuum cleaner button. when sending a report to the website that the vacuum cleaner tool is turned on. WEB only displays reports when the tool is turned on in the form of active tool time.